MODEL KOMUNIKASI ANTARETNIK DI PERBATASAN (Studi kasus Etnik Iban dan Melayu di Badau) - Ibrahim Ibrahim (Jurnal Al-Hikmah: Jurnal Dakwah, 2019)
In recent decades, the issue of ethnicity is an issue of lively chatter, especially regarding issues of social relations and conflicts often occur in many areas of the country, not least in West Kalimantan. In the interior of Kapuas Hulu, precisely in Badau, a form of ethnic communities can coexist in peace and harmony, namely ethnic Iban and Malays. Social history shows that there has been significant conflict between the two ethnics. It seemed to be an exception to some cases of ethnic conflict in the social history in West Kalimantan. Field research is found several factors that the reason for the establishment of good communication and harmonious inter-ethnic Iban and Malays in Badau. In the political aspect showed as shape of togetherness and good political cooperation in the form of "power sharing". In the aspect of social perceptions of his form a positive view of inter-ethnic. In terms of the reality of cultural values and acculturative accommodating culture of mutual understanding, respect and complement each other. In the experience of social interaction is also a manifestation of the form of social relations based on the spirit of togetherness, tolerance and mutual support the creation of a model of communication and relationships of peace and harmony among ethnic Iban and Malays in Badau. [Dalam beberapa dekade terakhir, persoalan etnik menjadi isu yang ramai dibincangkan, terutama menyangkut permasalahan hubungan sosial dan konflik yang kerap terjadi di banyak wilayah di tanah air, tak terkecuali di Kalimantan Barat. Di pedalaman Kapuas Hulu, tepatnya di Badau, wujud masyarakat etnik yang dapat hidup berdampingan dalam damai dan harmonis, yakni etnik Iban dan etnik Melayu. Sejarah sosial menunjukkan bahwa tidak pernah terjadi konflik yang berarti di antara kedua etnik tersebut. Hal ini seakan menjadi pengecualian terhadap beberapa kasus konflik etnik dalam sejarah sosial di Kalimantan Barat. Kajian di lapangan mendapati beberapa faktor yang menjadi alasan terbangunnya komunikasi yang baik dan harmonis antar etnik Iban dan Melayu di Badau. Dari aspek politik misalnya wujud kebersamaan dan kerjasama politik yang baik dalam bentuk ”sharing power”. Dari aspek persepsi sosial wujudnya pandangan yang positif antar etnik. Dari sisi budaya wujudnya nilai-nilai akomodatif dan akulturatif budaya yang saling memahami, menghargai dan mengisi satu sama lain. Dari sisi pengalaman interaksi sosial juga wujud satu bentuk hubungan sosial yang dilandasi pada semangat kebersamaan, toleransi dan saling mendukung terciptanya satu model komunikasi dan hubungan sosial yang damai dan harmonis antar etnik Iban dan Melayu di Badau] Kata kunci: Komunikasi, hubungan sosial, etnik, harmonisasi.